(untitled) (Research, Society and Development, 2021)
Seeking to understand the effects of increasing plant-1 bud load on solar radiation interception and its effect on bud fertility, the aim of this work is to evaluate the effect of increasing bud load on ’Sauvignon vines in relation to a interception of photosynthetically active writing and its effect on bud fertility in high altitude region of Santa Catarina. The present work was carried out during a 2016/2017 harvest, in a commercial vineyard, located in the municipality of São Joaquim. The treatments consisted of four different levels of bud loads: 15, 30, 50 and 75 buds plant-1. Buds were classified as fertile or non-fertile according to the presence or absence of the inflorescence. To evaluate the interception of photosynthetically active radiation, a ceptometer was used, and measurements were taken at midday during the phenological stages of full bloom, berry color change and maturity. The increase in plant-1 bud load reduces the fertility of basal buds, not influencing the fertility of medium and apical buds of the Sauvignon Blanc vine. There is a reduction in the photosynthetically active radiation of the Sauvignon Blanc vine as a function of the increase in plant-1 bud load, in the flowering, verison and harvesting phenological stages.